The Impact of Partner Reading and Text-based Discussion on Iraqi EFL Students' Literary Skills Development - Majid Bani Madhi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study verifies whether the  partner reading and text-based discussion has any impact on developing Iraqi EFL students' literary skills. The study focuses on   comprehension, interpretation, and critical analysis skills . The study adopted a mixed-methods quasi-experimental design applied to 120  high school students. The study  experimental  groups include  partner reading, text-based discussion, and their combination, and a control group taught by traditional instruction. Quantitative findings revealed the superiority of  the experimental groups  in all targeted literary skills. Remarkably, the combined approach attained the greatest improvements. Moreover,  qualitative findings revealed that the experimental groups  showed less language anxiety and more engagement. Furthermore , they   suggested  the importance of role-based management and teacher training for successful implementation in limited-resource classrooms. L1 use  and large class sizes were major issues in  implementing  partner reading and text-based discussion instruction . The study highlights the importance of  cooperative and collaborative strategies in  developing  literary skill acquisition in similar educational contexts  and this suggests modernizing EFL pedagogy in Iraq.DOI: https://doi.org/10.54633/2333-024-057-022